The Relationship Between Sportscape Towards Spectators’ Satisfaction and their Intentions to Repatronize Malaysian Football Cup at Stadium - Mohd Pilus, Asiah (2009)
The purpose of this study was to investige the relationship between sportscape towards spectators satisfaction and their intentions to repatronize Malaysian football Cup. The factors that were intended to analyze are motivation and loyalty towards the relationship between sportscape and spectators’ satisfaction and their intentions to repatronize Malaysian Football Cup at stadium.The study was conducted in Pennisular Malaysia with the involvement of 370 spectators who attended the Malaysian football Cup game from 12 stadiums. The study tools that were used are Sportscape Scale (Wakefield, Blodgett & Sloan, 1996), Motivation Scale For Sport Consumption (Trial & James, 2001), Model Point Of Attachment Index (Trail, Robinson & Dick, 2003), Customer Satisfaction (Hightower, Brady & Baker, 2002; Greenwell, Fink & Pastore, 2002) and Behavioral Intentions Scale (Hightower, Brady, Baker, 2002). Correlation Pearson, linear regression, hierarchical regression, path analysis and descriptive statistics (mean) were used to analyse data. The results also showed that motivation and loyalty have an influence on the relationship between spectators’ satisfaction and their intentions to repatronize football. Hierarchical regression analysis showed that sportscape influences only 3.4 percent of the variance on the spectators satisfaction. The combination of sportscape, motivation and loyalty variables predicts 56 percent variance regarding spectators’ satisfaction. Hierarchical regression analysis showed that sportscape influence only 5 percent of the variance on the intention to repatronize Malaysian Football Cup. The combination of sportscape, motivation and loyalty variables explained 59 percent of the variance regarding the intention to repatronize Malaysian football Cup. Path analysis showed that sportscape has and inderect influence on the motivation and loyalty as well as the spectators’ satisfaction and intention to repatronize Malaysian Football Cup. Besides sportscape, motivation and loyalty are identified other important factors in predicting spectators’ satisfaction and their intentions to repatronize Malaysian football Cup. Thus, Malaysian football associations and sport marketers should consider sportscape, motivation dan loyalty in planning marketing strategies to maximize attendance at Malaysian Football Cup. Therefore, Malaysian football associations and sport marketers should take further steps to increase the attendance and the revenue of the Malaysian football associations.